External institutional strategies for health care organizations as a quality strategy. (13th November 2019) - Berger, E; Groene, O; Shaw, C
Abstract: Accreditation, certification and supervision are quality strategies that intend to encourage the compliance of health care organizations with published standards through external assessment. The idea is that health care organizations will increase compliance with standards in advance of a planned external inspection. Despite several common characteristics of the three strategies, their origins and initial objectives differ. This presentation aims to disambiguate these concepts, inform on their utilization in European countries and discuss the evidence on their effectiveness, cost-effectiveness and implementation. External assessment strategies have been widely implemented in Europe. Most countries make use of several strategies, including basic supervision as part of the licensing process for healthcare providers, coupled with certification or accreditation strategies to ensure and improve the quality of care. The scope of these strategies and their regulation differs substantially between countries. Despite this widespread uptake, there is little robust evidence to support their effectiveness and there is a complete absence of evidence on cost-effectiveness. Furthermore, due to the broad purpose range of external assessments and the lack of consensus in the use of terminology, implementation strategies are sparse or missing. However, this presentation highlights several facilitators and barriers that may affect the implementation of external assessment strategies in health care organizations as well as relevant insights for policy-makers.